Evaluation of the Effect of Anterior Teeth Torque Values on the Space Occupied by Six Anterior Teeth: a Finite Element Analysis - Hosniye Zia-Edini; Bahare Fatemipour; Mohammad Mousavi; Hossein Darijani; Mohsen Moeini; Amin Dehghan (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Various factors have been introduced to achieve normal occlusion. One of them is anterior teeth torque that has a significant effect on orthodontic treatment outcomes. Purpose: The aim of this study was to investigate the effect of changes in anterior teeth torque on changes in the space occupied by six anterior teeth by using computer-aided three-dimensional interactive application (CATIA). Materials and Method: In this experimental finite element study, acrylic teeth with pre-adjusted MBT braces were aligned and three-dimensional (3D) scans were made by 3Dscaner. In the CATIA software program, upper incisors' torque was changed to -2, -4, -6, +2, +4 and+6 degrees and in the lower incisors to -1, - 3, -5, +3 and+5 degrees; the space was measured at 3 heights of maxillary incisor crowns and at incisal edges of mandibular incisors. Then maxillary incisors were then tapered and the measurements were made again. To evaluate the effect of tooth size, these procedures were carried out on teeth with +17% and -17% magnifications Results: The results showed that by increasing anterior torque from 14.7 to 20.7 degrees in maxillary incisors, the space occupied by anterior teeth increased. Maximum changes were at cingulum height with 1.421mm. Reduction in anterior torque from 14.7 to 8.7 degrees resulted in a decrease in this space and maximum changes were observed in the cingulum height with 1.824mm. In the mandibular arch, a 10-degree change in anterior torque resulted in an -.752mm change in the space. Changes in the space occupied by anterior teeth was not significant in tapered and normal teeth in +6 and -6-degree torque (p Value= 0.78 and p Value=0.83). Conclusion: By increasing or decreasing the incisors' torque, the space occupied by anterior teeth increased and decreased, respectively. These changes were less in tapered teeth. Size variations had no significant effect on the results.